Persepsi Generasi Muda Rumah Tangga Petani terhadap Budidaya Padi Sawah di Subak Piak, Kecamatan Penebel, Kabupaten Tabanan - WAYAN NOLY KURNYANTI; I WAYAN SRI ASTITI; I KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Perception Of Farmers 'Young Household Generation On Waste Rice CultivationIn Subak Piak,PenebelDistrict, Tabanan Regency The phenomenon of shifting labor in the agricultural sector, on average aged 40 yearsand over, young workers choose to work in the non-agricultural sector. Tend to choosejobs in sectors that can provide higher wages and are in urban areas. The study aimed toanalyze the perceptions of the young generation of farmer households on rice cultivationin Subak Piak, Penebel District, Tabanan Regency. The location determined usingdeliberate method with qualitative descriptive analysis method. The results of the studythat the perception of the young generation of farmer households in terms of social,economic and technical aspects are categorized as good. The social aspect, caring aboutthe existence and sustainability of the subak system and sekaa manyi, plunging into theagricultural sector does not have to be a farmer by becoming a broker, they still thinkthat being a farmer is less prestigious than jobs outside the sector. Economic aspects, thelevel of income in rice cultivation is not sufficient to meet all the needs of the familyrequires having a job other than the agricultural sector. Technical aspects, innovation inrice cultivation is needed so that yields increase. Subak Piak can involve the younggeneration of farmers in various activities such as upakara, ngembak toya, mutualcooperation in cleaning, maintenance of irrigation channels. Youth organizations canbecome a forum for young people to take part in various activities carried out by subakso that the presence and sustainabilityof subak and other traditional groups can still be maintained, even though they prefer or have more promising jobs than being farmers.